Integrating Systematic and Adaptive Curriculum Implementation: A Comparative Model for Inclusive 21st-Century Education - Eva Puspitasari; Ninik Wijiningsih; Rudi Susilana; Riche Cynthia Johan (Journal Evaluation in Education (JEE), 2026)
Purpose of the study: The purpose of this research is to compare various approaches in curriculum implementation and provide recommendations for further development. Methodology: Using qualitative method with a descriptive approach of field research. The subjects were secondary school teachers, while the informants were school principals. Subjects and informants were selected using purposive sampling, based on relevance and direct involvement in curriculum implementation. The research instruments included interview guidelines and observation sheets. Data were collected through in-depth interviews and direct observations at the school. The data were analyzed using thematic analysis to identify key themes and patterns from the interviews and observations. Main Findings: The findings of this study imply that curriculum development in the context of 21st-century education should not rely solely on rigid standardization or full flexibility, but rather on a strategic integration of systematic and adaptive approaches. Practically, schools are encouraged to strengthen curriculum management through structured planning, supervision, and the utilization of digital management systems such as MIS and LMS, while simultaneously providing pedagogical flexibility through differentiated and contextual learning that responds to students’ diverse needs and learning styles. For policymakers and school leaders, these results highlight the importance of developing curriculum policies that support both institutional accountability and instructional adaptability, particularly in promoting inclusive education for students with special needs. Novelty/Originality of this study: The novelty of this research lies in the comparison of two curriculum implementation approaches and the recommendation to integrate both to create a more effective, flexible, and contextual curriculum.